Project Based Learning Techniques to improve speaking skills - Herlina Dewi (Universitas Syiah Kuala, 2016)
This Classroom Action research was to describe the application of the Project Based Learning (PBL) technique through group work in teaching English especially for a speaking class in two cycles. Each cycle consisted of three meetings. The research was done in six major steps: preliminary preparations, planning, acting, observing, reflecting, and evaluating of the results of the teaching-learning speaking process. The instruments used in collecting the data were the researcher’s and the students’ observation sheets, tests, and student questionnaire sheets. The result from the first cycle was that the score for the researcher’s participation at the end of the first cycle was 73%, which is categorized as good; while after the second cycle the score was 90%, which is categorized as very good. With regard to the students’ participation, the percentage score after the first cycle was 70%, which is in the middle category. This increased significantly after the second cycle to 81% in the good category. Furthermore, the students’ improvement in speaking skills can be proved by comparing the results from the pre-tests and the post-tests. Their average score pre-teaching was 67, and post-teaching after the first cycle it rose to 71. Moreover, after the second cycle the students’ post-test result increased to 79. This means that the success indicator was reached. Consequently, PBL technique can improve the students’ speaking skills. Finally, data from the questionnaire shows that 90% of the students chose the options “agree” and “strongly agree” to the use of the PBL technique in their speaking class. They also responded positively to the use of the PBL technique in the process of teaching-learning speaking.